2010
DOI: 10.2478/s11756-009-0230-4
|View full text |Cite
|
Sign up to set email alerts
|

Localization of prolactin receptor in the dorsal and ventral skin of the frog (Rana ridibunda)

Abstract: Abstract:The dorsal and ventral skin in amphibians plays an important role in osmoregulation. Prolactin hormone is involved in regulation of amphibian skin functions, such as water and electrolyte balance. Therefore, amphibians may be useful as a model for determining the sites of the prolactin receptor. In this study, prolactin receptor was detected in frog dorsal and ventral skin using immunohistochemical staining method. Prolactin receptor immunoreactivity was localized in all epidermal layers except stratu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…This may be due to the greater initial abundance of bacteria (and to some extent, fungi) on the ventrum than the dorsum, possibly arising from the greater fluxes of water and solutes experienced across the ventral surfaces of frogs, leading to richer and more abundant bacterial communities ( 40 ), as well as from the greater contact between the ventral surfaces and the substrates, leading to greater exposure to microbes in the environment. In addition, mucous and serous glands are asymmetrically distributed across the skin of Phyllomedusinae frogs ( 40 42 ), with higher concentrations of serous glands on the dorsal surfaces and greater abundances of mucous glands on the ventral surfaces ( 43 45 ). The biochemicals (e.g., peptides and glycosaminoglycans) produced by both gland types are likely to influence the bacterial community associated with either surface of the skin of frogs ( 40 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to the greater initial abundance of bacteria (and to some extent, fungi) on the ventrum than the dorsum, possibly arising from the greater fluxes of water and solutes experienced across the ventral surfaces of frogs, leading to richer and more abundant bacterial communities ( 40 ), as well as from the greater contact between the ventral surfaces and the substrates, leading to greater exposure to microbes in the environment. In addition, mucous and serous glands are asymmetrically distributed across the skin of Phyllomedusinae frogs ( 40 42 ), with higher concentrations of serous glands on the dorsal surfaces and greater abundances of mucous glands on the ventral surfaces ( 43 45 ). The biochemicals (e.g., peptides and glycosaminoglycans) produced by both gland types are likely to influence the bacterial community associated with either surface of the skin of frogs ( 40 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…FSHR and LHR in mammals and amphibians were also highly conserved during evolution of vertebrates [ 33 ]. Finally, a mouse anti-PRLR antibodies was used to study the frog Rana ridibunda protein [ 34 ]. These different data allowed us to consider that human anti-steroid or anti-pituitary receptor antibodies can be used for immunolocalization of amphibian hormone receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Indirect immunohistochemical method has been chosen to localize hormone receptors. Several studies have shown there was an acceptable conservation of the biochemical composition of antibodies in all vertebrates [ 1 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ]. According to these studies, we have chosen to use antibodies generally used to detect the hormones in several animal species.…”
Section: Methodsmentioning
confidence: 99%
“…It has been found that cell proliferation, apoptosis and cell differentiation are involved in the tissue remodeling of the oviduct during the sexual cycle of amphibians [7]. Prolactin (PRL) is another hormone also involved in various aspects of reproduction in amphibians [20,34]. In particular, PRL together with sex steroids are necessary for the structural development and formation of oviductal secretions [35,18].…”
Section: Reproductive Biology Of Caeciliansmentioning
confidence: 99%